The Influence of Self-Efficacy, Supervision and Organizational Commitment on the Performance of Satpol PP Employees in Bengkulu Province - Afifah, Luthfiyah; Widodo, Slamet (Universitas Pamulang, 2024)
In maintaining public security and order, the Pamong Praja Police Unit is indispensable. The purpose of this study is to examine the elements that affect the performance of Satpol PP. This study focuses on self-efficacy, supervision, and organizational commitment as variables that are considered to play a role. This type of research is quantitative research and the data analysis method uses SPSS 25 software for windows. The population used includes all Satpol PP employees in Bengkulu Province. The sampling technique in this study used saturated sampling / census sampling technique with a total sample size of 223 respondents using quantitative methods. The results of the research analysis show that the self-efficacy variable (X1) has a positive and significant effect on performance (Y), the supervision variable (X2) has no positive and significant effect on performance (Y), the organizational commitment variable (X3) has a positive and significant effect on performance (Y), and the variables of self-efficacy, supervision and organizational commitment together have a positive and significant effect on performance (Y).